Problems identification and improvement path of China’s marine ecological compensation legal system - Wang, Tao (Frontiers in Marine Science, 2023)
In China’s marine industry, which has been growing quickly over the past few years, marine ecological compensation has been a critical framework for safeguarding the marine environment. Through the text analysis of the China’s marine ecological compensation legal system, this study found that there are multiple defects in it, including institutional supply shortage leads to lack of coordination and dispersion in China’s marine ecological compensation legislative system, the absence of legislative concept of ‘land-sea overall planning’ in China’s marine ecological compensation legal system, limited scope of China’s marine ecological compensation, lack of clear standards for marine ecological compensation, the relationship between marine planning and the marine ecological compensation system is not straightforward, and insufficiency of regulation on the marine ecological compensation. The paper suggests that priority should be given to developing a multi-level legal system for compensating marine ecological damage, the legal method of achieving ‘land-sea overall planning’ and a compensation mechanism that combines a variety of compensation methods with a scientific and reasonable standard should be established within China’s ecological compensation legal system, marine ecological compensation should be incorporated into marine planning and the separation of powers and implementation of the marine ecological compensation regulation should be enhanced.